DETERMINANTS OF NON-OIL AND GAS IMPORT VALUE IN INDONESIA - Tsani, Luthfi Ibnu; Andryan Setyadharma; Ahmad Syahrul Fauzi; Rasyad Nu'man (Business and Economic Analysis Journal, 2025)
Indonesia continues to rely heavily on imports, particularly non-oil and gas imports, which can threaten economic stability. However, existing studies rarely examine how domestic macroeconomic indicators jointly affect this dependency. This study aims to fill that gap by analyzing the influence of money supply (M2), BI Rate, and inflation rate on the value of non-oil and gas imports in Indonesia. Using monthly time series data from 2020 month 1 to 2023 month 4 (40 observations), this study employs a multiple linear regression model to evaluate both partial and simultaneous effects of the three independent variables. The results show that money supply (M2) and inflation rate have a significant positive impact. In contrast, the BI Rate significantly affects the value of non-oil and gas imports. These findings suggest that increased liquidity and rising inflation may stimulate import activity, while higher interest rates tend to suppress it. The study provides important insights for Bank Indonesia and policymakers in designing macroeconomic strategies to stabilize the import sector. Strengthening the coordination of monetary and fiscal policies is recommended to manage import growth while maintaining economic stability.